Spiritual Benson Relaxation in Reducing Stress in Patients Undergoing Hemodialysis - Tata Mahyuvi; Noer Istiqomah; Yuly Peristiowati; Katmini; Joko Prasetyo; Indasah; Hari Prasetyo Umar (Journal Of Nursing Practice, 2023)
Background:  Patients with chronic kidney failure experience various changes in their lives, starting from their diet, exercise, blood sugar control, urea, creatinine and renal function replacement therapy that must be carried out throughout their lives, causing long stress for the patient. Purpose: The purpose of this study was to analyze the effect of Spiritual Benson Relaxation on reducing stress in patients undergoing hemodialysis. Methods: This research design uses quasi-experimental approach with a pre and post control group design. The population of all patients with chronic kidney failure who underwent dialysis in the Hemodialysis unit of the Surabaya Islamic Hospital A. Yani was 70 people. The sample size is 32 respondents. The sampling technique is purposive sampling. The intervention group was given Spiritual Benson Relaxation and the control group were given intervention according to hospital standards. The analysis used the  Wilcoxon with a significant value of . < 0.05. Results: The results showed that the stress level p value 0.001 in the intervention group and the control group p value 0.035 which means that there is an effect of Spiritual Benson Relaxation on reducing stress in patients undergoing hemodialysis. Conclusion: Spiritual Benson Relaxation is effective in reducing stress in patients undergoing hemodialysis and the technique is easy to do.